Ground beef from electrically stimulated and pre-rigor processed carcasses - Hunt, Melvin C.; Kendall, J.L.A.; Kropf, Donald H.; Dikeman, Michael E.; Kastner, Curtis L. (Kansas State University. Agricultural Experiment Station, 2011)
Ground beef from electrically stimulated and/or pre-rigor processed carcasses was equivalent to conventional ground beef in texture, palatability, and frozen storage stability, but lost more juice when vacuum-stored, had 2% more total cooking losses from patties, and 1 day less shelf life during display.
Keywords: Beef; Electrical stimulation; Pre-rigor; Carcass